Survival of Elderly Patients Undergoing Percutaneous Coronary Intervention for Acute Myocardial Infarction Complicated by Cardiogenic Shock - Lim, H.; Farouque, O.; Andrianopoulos, N.; Yan, B.; Lim, C.; Brennan, A.; Reid, Christopher; Freeman, M.; Charter, K.; Black, A.; New, G.; Ajani, A.; et al. (2009)
Objectives: We sought to assess clinical outcomes of elderly patients (age =75 years) undergoing percutaneous coronary intervention (PCI) for acute myocardial infarction (MI) complicated by cardiogenic shock (CS) in a contemporary multicenter PCI registry. Background: Although benefits of early PCI have been shown in younger groups, few studies have reported on clinical outcomes in elderly shock patients using current PCI techniques. Methods: We analyzed baseline characteristics and procedural and clinical outcomes in 143 consecutive patients presenting with MI and CS who underwent PCI from the Melbourne Interventional Group registry between 2004 and 2007. Results: Of the 143 patients, 31.5% (n = 45) were elderly and 68.5% were younger (age <75 years). Elderly patients were more likely to be female (46.7% vs. 22.4%, p < 0.01) and have hypertension (77.8% vs. 46.4%, p < 0.01), previous MI (31.1% vs. 15.5%, p = 0.03), renal failure (24.4% vs. 11.3%, p < 0.05) and multivessel coronary artery disease (93.1% vs. 68.3%, p < 0.01). Stent (86.7% vs. 94.8%, p = 0.09), glycoprotein IIb/IIIa inhibitor (68.9% vs. 65.3%, p = 0.67), and intra-aortic balloon pump (57.8% vs. 58.2%, p = 0.97) use were similar in both groups. In-hospital, 30-day, and 1-year mortality in the elderly group versus the younger group were 42.2% vs. 33.7% (p = 0.32), 43.2% vs. 36.1% (p = 0.42), and 52.6% vs. 46.8% (p = 0.56), respectively. Conclusions: In this study, the 1-year survival of elderly patients with acute MI complicated by CS undergoing PCI was comparable to younger patients. These data suggest that in elderly patients presenting with CS, benefit is possible with selective use of early revascularization and merits further investigation. © 2009 American College of Cardiology Foundation.